Interactive Multiresolution Visualization of Cellular Network Processes - Ortega, Oscar O.; Lopez, Carlos F. (iScience, 2020)
Visualization plays a central role in the analysis of biochemical network models to identify patterns that arise from reaction dynamics and perform model exploratory analysis. To facilitate these analyses, we developed PyViPR, a visualization tool that generates static and dynamic representations of biochemical network processes within a Python-based environment. PyViPR embeds network visualizations within Jupyter notebooks, thus enabling integration with modeling, simulation, and analysis workflows. To present the capabilities of PyViPR, we explore execution mechanisms of extrinsic apoptosis in HeLa cells. We show that community-detection algorithms identify groups of molecular species that capture key biological functions and ease exploration of the apoptosis network. We then show how different kinetic parameter sets that fit the experimental data equally well exhibit significantly different signal-execution dynamics as the system progresses toward mitochondrial outer-membrane permeabilization. Therefore, PyViPR aids the conceptual understanding of dynamic network processes and accelerates hypothesis generation for further testing and validation. [Display omitted] •Static and dynamic interactive visualizations of systems biology models•Community detection algorithms are used to facilitate network exploration•Visualization embedded in Jupyter Notebooks for easy model pipeline dissemination•Support for multiple graph formats including GraphML, SBGN, and SIF Integrative Aspects of Cell Biology; Bioinformatics; Systems Biology